An Overview of the International Copper Association's Pre-Competitive R&D Portfolio of Copper Related Technologies - H. Stillman (Canadian Institute of Mining, Metallurgy and Petroleum, 2007)
The International Copper Association, Ltd. (ICA) is responsible for guiding strategy and policy, and funding international initiatives that help deliver the benefits of copper around the world. ICA's technology initiative supports this mission by funding pre-competitive technology development and accelerating the commercialization of new copper-related technologies. The R&D portfolio includes some projects that defend existing applications such as plumbing tube and data cabling, but the majority of projects are designed to enable new applications for copper. The current technology portfolio is focused on leveraging copper's unique electrical, thermal, mechanical and antimicrobial properties to define and expand the role of copper in areas poised for future technological growth: reducing disease transmission, sustainable energy generation, reducing the environmental impact of production processes, and in increasing energy efficiency. Projects related to these areas are conducted at qualified external organizations including universities, early-stage firms, and large OEMs worldwide. This talk will provide an overview of ICA's technology initiative's principles, projects and partnerships to stimulate the audience to think about copper-related innovations.